Structure–function analysis of tRNA(Gln) in an Escherichia coli knockout strain - MCCLAIN, WILLIAM H. (Copyright 2004 by RNA Society, 2004)
The diverse and highly specific interaction between RNAs and proteins plays an essential role in many important biological processes. In the glutamine aminoacylation system, crystal structures of the free and ligated macromolecules have provided a description of the tRNA–protein interactions at the molecular level. This data lays the foundation for genetic, biochemical, and structural analyses to delineate the set of key interactions that governs the structure–function relationships of the two macromolecules. To this end the chromosomal tRNA(Gln) genes were disrupted in Escherichia coli to produce a tRNA(Gln) knockout strain that depends upon expression of a functional tRNA(Gln) from a plasmid for cell viability. Mutants of an inactive tester tRNA derived from tRNA(Ala) were generated by hydroxylamine mutagenesis, and the active derivatives were selected by their ability to support knockout cell growth. Two of the mutants contained substitutions in the first base pair of the acceptor stem that likely facilitate the formation of a hairpin loop that places A76 in the active site. The third mutation was located at position 13 in the D loop region of the tRNA, and suggests that an interaction with residue 13 contributes to a specific conformational change in unliganded GlnRS, which helps configure the enzyme active site in its catalytically proficient form. This work demonstrates the efficacy of an integrated approach that combines genetic selections and biochemical analyses with the physical data from crystal structures to reveal molecular steps that control the specificity of RNA–protein interactions.